2011
DOI: 10.1111/j.1463-6409.2011.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prospecting for cryptic species in Phyllodistomum lacustri (Platyhelminthes, Gorgoderidae)

Abstract: de Leó n, G. (2011). Molecular prospecting for cryptic species in Phyllodistomum lacustri (Platyhelminthes, Gorgoderidae). -Zoologica Scripta, 40, 296-305. Partial sequences of the 28S ribosomal RNA and cytochrome c oxidase I (COI) genes were compared among populations of a widely distributed and morphologically uniform digenean species in North America, Phyllodistomum lacustri, a parasite characteristically associated with ictalurid catfishes. Specimens were collected from the urinary bladder of ictalurid hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…In some systems, such observations have led to suggestions that apparently generalist parasites be provisionally treated as complexes of cryptic host specialists until confirmation with molecular data (Locke et al 2010b, Miller et al 2011). In the present case, despite intensive sampling, molecular data probably underestimate local diplostomoid diversity in one of the six fish species (Locke et al 2010b) and host-specific cryptic species have also been found in additional parasite taxa related to those we encountered (Steinauer et al 2007, Rosas-Valdez et al 2011. Therefore, if anything, we may have underestimated the effect of genetic distance between host species.…”
Section: Discussionmentioning
confidence: 54%
“…In some systems, such observations have led to suggestions that apparently generalist parasites be provisionally treated as complexes of cryptic host specialists until confirmation with molecular data (Locke et al 2010b, Miller et al 2011). In the present case, despite intensive sampling, molecular data probably underestimate local diplostomoid diversity in one of the six fish species (Locke et al 2010b) and host-specific cryptic species have also been found in additional parasite taxa related to those we encountered (Steinauer et al 2007, Rosas-Valdez et al 2011. Therefore, if anything, we may have underestimated the effect of genetic distance between host species.…”
Section: Discussionmentioning
confidence: 54%
“…Reliable revision of the genus Phyllodistomum appears dependent on the accumulation of molecular data. ITS2 and 28S rDNA sequences have been used extensively in trematode taxonomy, and in particular, these sequences have been widely employed in gorgoderid studies (Petkevi ci ut_ e et al 2004;Bolek et al 2009;Cutmore et al 2010Cutmore et al , 2013Rosas-Valdez et al 2011) and now provide the most diverse database of molecular characters.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, many of them having been published in JP, have revealed several cryptic species of trematodes (within the genera Clinostomum, Crassicutis, Oligogonotylus, Phyllodistomum) and acanthocephalans (Neoechinorhynchus, Pomphorhynchus) (Pe´rez-Ponce de Leo´n et al, 2008;Martı´nez-Aquino et al, 2009;Razo-Mendivil et al, 2010;Rosas-Valde´z et al, 2011;Garcı´a-Varela et al, 2012;SerenoUribe et al, 2013). Biogeographical studies are focused on unravelling relationships of the Mexican fauna of helminth parasites with that of the northern part of North America and Central America, and they search for general patterns and processes of formation of the parasite fauna (Vidal-Martı´nez and Kennedy, 2000;Aguilar-Aguilar et al, 2003; Pe´rez-Ponce de Choudhury, 2002, 2005; Pe´rez-Ponce de Leo´n et al, 2013).…”
Section: Geography Of Knowledgementioning
confidence: 95%